2008
DOI: 10.2337/db07-1162
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Inhibits Blood-Brain Glucose Transfer in Humans

Abstract: OBJECTIVE-Glucagon-like peptide-1 (GLP-1) has many effects on glucose homeostasis, and GLP-1 receptors are broadly represented in many tissues including the brain. Recent research in rodents suggests a protective effect of GLP-1 on brain tissue. The mechanism is unknown. We therefore tested whether these neuroprotective effects could relate to changes of glucose transport and consumption.RESEARCH DESIGN AND METHODS-We studied 10 healthy men in a randomized, double-blinded, placebo-controlled cross-over experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 46 publications
2
36
1
Order By: Relevance
“…In contrast to previous studies that infused GLP-1 during pancreatic euglycemic (12) and hyperglycemic clamps (13), our study evaluated the effect of GLP-1 under physiologic conditions by combining 18 F-FDG with stable isotope tracer infusion during OGTT and quantitated CMR glu , RaO, and RaT. We found that RaO and RaT were inversely correlated with CMR glu but only after EX and not after PLC.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…In contrast to previous studies that infused GLP-1 during pancreatic euglycemic (12) and hyperglycemic clamps (13), our study evaluated the effect of GLP-1 under physiologic conditions by combining 18 F-FDG with stable isotope tracer infusion during OGTT and quantitated CMR glu , RaO, and RaT. We found that RaO and RaT were inversely correlated with CMR glu but only after EX and not after PLC.…”
Section: Discussioncontrasting
confidence: 38%
“…The protocol reflects the effect of normal route of subcutaneous EX administration on the normal route of glucose administration (oral). Previous studies used intravenous infusion of glucose, GLP-1, and somatostatin, and found a trend to decrease in CMR glu during normoglycemia (12) and an increase in CMR glu during hyperglycemia (13). However, in the Gejl et al (13) study, insulin concentrations were three times those observed during PLC, and thus a separate effect of insulin could not be excluded.…”
Section: Discussionmentioning
confidence: 42%
“…Also, recently published data have implicated adiponectin in regulating food intake and energy expenditure [48,49]. Moreover, glucagon-like peptide-1 (GLP-1), which is synthesized in the brain as well [50,51], may also be involved. Therefore, future research should attempt to investigate the correlations between these hormones/adipokines and regional brain activation using a similar fMRI paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Sulfonylureas were discontinued 3 days prior to examination, and metformin was discontinued on the day of examination. In order to study the effects of GLP-1 receptor activation per se, i.e., independent of hormonal or metabolic changes induced by GLP-1 receptor activation, all measurements were performed during a somatostatin pancreatic-pituitary clamp according to principles previously described (20). In short, somatostatin (Somatostatin; Eumedica) was infused at a rate of 60 ng/kg/min to suppress endogenous insulin, glucagon, growth hormone, and GLP-1 production.…”
Section: Experimental Designmentioning
confidence: 99%